Insights into vase-shaped microfossil diversity and Neoproterozoic biostratigraphy in light of recent Brazilian discoveries. (July 2019) - Morais, L.; Lahr, D.J.G.; Rudnitzki, I.D.; Freitas, B.T.; Romero, G.R.; Porter, S.M.; Knoll, A.H.; Fairchild, T.R.
Abstract: Vase-shaped microfossils (VSMs) occur in dolostone clasts within conglomerates, breccias, and diamictites of the Neoproterozoic Urucum Formation, Jacadigo Group, southwest Brazil. Although their taphonomic history is distinct from those of other VSM assemblages, morphometric comparison of Urucum fossils with five others described previously from North America and Europe show that two of the Urucum species—the long-necked Limeta lageniformis Morais, Fairchild, and Lahr in Morais et al., 2017 and the funnel-necked Palaeoamphora urucumense Morais et al., 2017—occur in the Kwagunt and Callison Lake assemblages, as does Pakupaku kabin Riedman, Porter, and Calver, 2017 recently described from the Togari Group, Tasmania. Obelix rootsii (Cohen, Irvine, and Strauss, 2017) new combination, previously known only from the Callison Lake Formation, is documented here from the Kwagunt Formation. In addition, Trigonocyrillium horodyskii (Bloeser, 1985) and Bonniea dacruchares Porter, Meisterfeld, and Knoll, 2003, first described from the Kwagunt assemblage, have now been found in the Urucum Formation. In light of this survey, 16 of the 18 validly described VSM species are now known to occur in the Kwagunt Formation and 13 in the Callison Lake Formation, with 12 of them shared by both formations. The fact that the Urucum VSM assemblage exhibits six of seven species in common with the Kwagunt Formation— L. lageniformis, P. urucumense, Cycliocyrillium simplex Porter, Meisterfeld, and Knoll, 2003, C. torquata Porter, Meisterfeld, and Knoll, 2003, B. dacruchares Porter, Meisterfeld, and Knoll, 2003, and T. horodyskii (Bloeser, 1985)—and all but the last of these in common with the Callison Lake Formation supports correlation of these three assemblages and indicates that the source of the fossiliferous clasts within the Urucum Formation may well have been a now-vanished late Tonian carbonate platform. UUID: http://zoobank.org/ac0becd6-29ff-4491-80fa-0291730fba65